Effects of Sodium Trimetaphosphate, Associated or Not with Fluoride, on the Composition and pH of Mixed Biofilms, before and after Exposure to Sucrose - Cavazana, Thamires Priscila [UNESP]; Pessan, Juliano Pelim [UNESP]; Hosida, Thayse Yumi [UNESP]; Sampaio, Caio [UNESP]; Amarante, Viviane de Oliveira Zequini [UNESP]; Monteiro, Douglas Roberto; Delbem, Alberto Carlos Botazzo [UNESP] (Karger Publishers, 2020)
The aim of the present study was to evaluate the influence of sodium trimetaphosphate (TMP), associated or not with fluoride (F), on the concentrations of F, calcium (Ca), and phosphorus (P) and on the pH of mixed biofilms of Streptococcus mutans and Candida albicans, before and after exposure to sucrose. The biofilms received three treatments (72, 78, and 96 h after the beginning of their formation), at three TMP concentrations (0.25, 0.5, or 1%), with or without F at 500 ppm. Solutions containing 500 and 1,100 ppm F as well as artificial saliva were also tested as controls. Biofilm pH was measured and the concentrations of F, Ca, and P were determined (solid and fluid phases). In a parallel experiment, after the third treatment (96 h), the biofilms were exposed to a 20% sucrose solution to simulate a cariogenic challenge and the pH of the medium, F, Ca, P, and TMP were determined. The data were submitted by two-way ANOVA, followed by Fisher's least significant difference test (p < 0.05). Treatment with TMP and 500 ppm F led to higher F concentration in the biofilm fluid. Although TMP did not affect Ca concentrations, biofilms treated with TMP alone presented higher P concentrations. Treatment with 1% TMP and F led to the highest pH values of the biofilm, both before and after the cariogenic challenge. It was concluded that TMP increases F and P in the biofilm and that its presence promotes an increase in the pH of the medium, even after the cariogenic challenge.
Keywords: Biofilms; Candida albicans; Fluorides; Phosphate; Streptococcus mutans